(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Cerebral stroke (ONMK) is a leading cause of morbidity and mortality worldwide, with far-reaching systemic consequences. Among the less explored but critical areas is the relationship between stroke and liver function. This article investigates the complex interplay between stroke-induced brain damage and hepatic function, emphasizing the pathophysiological mechanisms that link cerebral ischemia to liver dysfunction. The discussion includes insights into the metabolic, inflammatory, and oxidative stress responses that affect both organs, highlighting the importance of integrated care in stroke management.